KEBIJAKAN DIVIDEN, REAKSI PASAR, DAN STRUKTUR KEPEMILIKAN: STUDI EMPIRIS PADA BURSA EFEK INDONESIA - , Ari Gayo ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study analyzes the market reaction to dividend policy for the period 2004 to 2010 at Indonesia Stock Exchange. Dividend policy can be seen from dividend change announcement, does the company payments increase or decrease from the previous period. Event study methodology is applied to see the market reaction of dividend policy the company. The results showed that when the company announced a dividend increase, market will respond positively, otherway when the company announced a dividend decrease, market will respond negatively. This fact also supports the rent extraction hypothesis because the market interprets that in companies that pay increasing dividends have the controlling shareholder, who do not want to make the exploitation of minority shareholders, and vice versa. The results of this study also supports the dividend signaling theory which states that the payment of dividends have information content about future profitability.